FIGURATIVE ART TOOLS IN THE NOVEL "THE ADVENTURES OF TOM SAWYER" BY MARK TWAIN. - Isomiddinova Shohsanam Ortiq qizi ,; Azzamova Nigora , (TADQIQOTLAR.UZ, 2024)
Abstract: The Adventures of Tom Sawyer by Mark Twain is a classic American novel that is known for its rich use of figurative language and literary devices. As a work of realist fiction, the novel employs various tools of figurative art to convey its themes, characters, and the setting of 19th century small-town America. The book The Adventures of Tom Sawyer by Mark Twain has lots of pathos and deeply affects many readers. personification-n. the attribution of human nature or character to animals, inanimate objects, or abstract notions, especially as a rhetorical figure.